Scenarios For Limiting The Veto of Permanent Members Of The United Nations Security Council - Kasim, Aksah; Suhariyanto, Didik; Ramdhani, Wahyu; Rahim, Erman I; Danial, Danial (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The UN's principal mission is to promote international stability and peace. To that end, the UN established the Security Council, its governing body with last say on the subject. The United States, Russia, China, and France—the five most militarily competent nations—are veto-wielding permanent members of the United Nations Security Council. The fundamental objective of this research is to determine the impact of veto power on the function of the United Nations Security Council in maintaining global peace and security. In that case, will we be attempting to have a lex expert on the right to veto? This work is classified as normative research. The results showed that the veto did not improve the Security Council's performance. The ability to veto decisions made by the Security Council on how to address critical international crises means that the council isn't always effective. Legal rules should be put in place to ensure that the right to veto as a controller is not misused and fulfils its original purpose. The power to reject a resolution in situations involving crimes against humanity or genocide is an important part of the veto system, as is the two-year limit on each non-permanent member's use of the veto, and the limitation of veto use to a single case if discussed consecutively in Security Council meetings.